TINDAKAN ORANGTUA DALAM MENYEKOLAHKAN ANAK BERKEBUTUHAN KHUSUS PADA LAYANAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR NEGERI 1 TANJUNG KECAMATAN PURWOKERTO SELATAN KOTA PURWOKERTO - Ankarlina Pandu Primadata; RB Soemanto; Bagus Haryono (UNIVERSITAS SEBELAS MARET (UNS), 2015)
Education is the right for every Indonesian citizens, include the education for children with special needs (disability). Every parents who has child like this has aproblem in looking for special schools in order to give a good education for theirchildren for their child. It becomes a dilemma for every parents to send their child tothe special school or public school. The purpose of this research to figure howactions of parents in educating children on inclusive education services, as well as todescribe the actions of parents in educating children with special needs in inclusiveschool SDN 1 Tanjung, Purwokerto. This research was done in Purwokerto, precisely at SDN 1 Tanjung. This study usesqualitative method with case study strategy. The sampling technique used waspurposive sampling technique, the main informants were parents of students withspecial needs in SDN 1 Tanjung. Data collection techniques used in this study is indepthinterviews, indirect observation technique (Non-participatory observation)and document analysis techniques. The validity of the data in this study include source triangulation, triangulation method and review the informant. In this study,the interactive model was used for the analysis of the data. The results showed that there are internal and external factors that influence theactions of parents who have child with special needs in determining education fortheir children. In addition, parentsactalsodivided intofourtypesofactionasdictatedbyMaxWeber. These actionsareinstrumentalrationalaction,whichactsasa parenthas hopesand dreamsfor their children, sotheysend theirchildren topublicschoolsthatprovideformaleducationinclusive. Action secondly isrational action gets value orientation, which is action which done by parent bymerges ethical points, esthetic and religious in its child education that gets specialneeds. Third act is afektif action which is action which done by parent because moodor feel, severally parent gets that assumption its child doesn't child get specialneeds, they finally are opting school by service inclusive education thanextraordinary school. The last act is traditional action where parent school its childbecause vicinity environment charge. Happening interaction in social life parentsstudent gets special requirement result many signification symbols as lingual as.Symbol as lingual as in such event information that is passed on to student parentgets special requirement that is be next at interpretation by parents by undertakingaction school its child on inclusive school service Keyword: child with special needs, parent, inclusive education service, social action, interactionisme symboli